2021
DOI: 10.3389/fendo.2021.749609
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of the MHC Class I Gene in Thyroid Cells: Role of the Promoter “Tissue-Specific” Region

Abstract: In previous studies we have demonstrated that the expression of the Major Histocompatibility Complex (MHC) class I gene in thyrocytes is controlled by several hormones, growth factors, and drugs. These substances mainly act on two regions of the MHC class I promoter a “tissue-specific” region (−800 to −676 bp) and a “hormone/cytokines-sensitive” region (−500 to −68 bp). In a previous study, we have shown that the role of the “tissue-specific” region in the MHC class I gene expression is dominant compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…In this respect, Giuliani et al demonstrated that MHC reduction was associated with high levels of TGF-β1, and αand γ-interferons (IFNs). Other negative MHC regulators included insulin and insulin-like growth factor receptor (IGF)-1, Thyroid Stimulating Hormone (TSH), methimazole, phenyl methimazole, thymosin-α1 and glucose [29].…”
Section: Tme In Tc: Immune Cells Inflammatory Mediators and Stromamentioning
confidence: 99%
“…In this respect, Giuliani et al demonstrated that MHC reduction was associated with high levels of TGF-β1, and αand γ-interferons (IFNs). Other negative MHC regulators included insulin and insulin-like growth factor receptor (IGF)-1, Thyroid Stimulating Hormone (TSH), methimazole, phenyl methimazole, thymosin-α1 and glucose [29].…”
Section: Tme In Tc: Immune Cells Inflammatory Mediators and Stromamentioning
confidence: 99%